Cyber Threats Management Strategy for Thailand - ผกามาศ พงษ์ศักดิ์; ประสงค์สร้าง ชัยวัฒน์; ชัยสนิท เศรษฐชัย; ช่วยเพชร ชูเกียรติ; อรุณรังสี ราชิต (FOYER: The Journal of Humanities, Social Sciences, and Education, 2022)
This article presents a strategy for managing cyber threats for Thailand, with the following objectives: 1) study the model of the situation assessment method in Thailand; 2) study the impact of cyber threats on national security; and 3) present a cyber threats management strategy for Thailand. This research uses qualitative research methodology by study focused on specific issues leading to the establishment of cyber threat management strategies in Thailand. Target groups include: 1) state security agencies; 2) ministries concerned 5 ministry 3) local administrators/leaders; 4) private sector organizations; 5) people in Thailand; 6) news officers threatened of cyber threats; 7) military officers threatened of cyber threats; 8) people involved in internet network; 9) experts from the cyber security department, Thai Army Headquarters; and 10) ICT and cyber security experts in the southern region Thailand. The total target groups of 79 people came from a specific selection. The research tools were unstructured interviews. Analysis and synthesis of data based on qualitative research. Analysis and synthesis of qualitative research data by means of analytical descriptive method, Validate data using data triangulation technique and confirm the strategy by using connoisseurship approach. The research found that in Thailand, there is a cybercrime process to create a variety of disturbances. Like using social networks to undermine the credibility of government officials. Including the psychological operations and propaganda of the poor. Creating negative news and creating conflicts with the people. Sabotage using the Internet is mediocre. There are likely to be other types of operations. In addition, the system uses communication through the application to avoid detection and tracking by government officials. These have made a direct impact on national security. Strategies for managing cyber threats for Thailand consist of 7 strategies: 1) Thailand’s infrastructure for dealing with cyber threats; 2) creating cyber awareness for the people; 3) development of cyber security; 4) promotion of cyber-cooperation between the public, private and public sectors; 5) enforcement of cyber ​​law and enforcement with the people; 6) use of mutual Integration to share information and 7) cyber ​​awareness for prevention, inhibition and attack. For Thailand, strategies and measures to address cyber threats should be implemented to ensure consistency, quality and consistency. In order to strengthen cyber security of the country.